2021
DOI: 10.3390/jpm11100971
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy Biomarkers for Immunotherapy in Non-Small Cell Lung Carcinoma: Lessons Learned and the Road Ahead

Abstract: Over the recent years, advances in the development of anti-cancer treatments, particularly the implementation of ICIs (immune checkpoint inhibitors), have resulted in increased survival rates in NSCLC (non-small cell lung cancer) patients. However, a significant proportion of patients does not seem respond to immunotherapy, and some individuals even develop secondary resistance to treatment. Therefore, it is imperative to correctly identify the patients that will benefit from ICI therapy in order to tailor the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 141 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…Treatment with CCX559 increased the level of plasma sPD-L1, which reflects both exosomal PD-L1 and the extracellular domain that is shed from the cell surface by matrix metalloproteases. Increased blood levels of sPD-L1 have been observed in cancer, autoimmunity, inflammation, and pregnancy [ 1 , 22 ], possibly as a consequence of PD-L1’s role in maintaining peripheral homeostasis [ 1 , 23 ]. A number of cytokines, including IFNγ, have been shown to increase sPD-L1 levels in vitro and in vivo [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with CCX559 increased the level of plasma sPD-L1, which reflects both exosomal PD-L1 and the extracellular domain that is shed from the cell surface by matrix metalloproteases. Increased blood levels of sPD-L1 have been observed in cancer, autoimmunity, inflammation, and pregnancy [ 1 , 22 ], possibly as a consequence of PD-L1’s role in maintaining peripheral homeostasis [ 1 , 23 ]. A number of cytokines, including IFNγ, have been shown to increase sPD-L1 levels in vitro and in vivo [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [279] have demonstrated that it is necessary a high-quality DNA to avoid underestimation of TMB for a correct clinical evaluation. Chauhan et al [280] have detected and calculated the TMB from the ctDNA in urine rather than in blood [281]. Although many different guidelines (such as NCCN and ESMO guidelines) do not address plasma-based testing TMB or other tumor agnostic biomarkers like neurotrophic tyrosine receptor kinase (NTRK), the ctDNA analysis can help to choose the best treatment in selected cases [194].…”
Section: Treatment Selection and Resistant Mechanismsmentioning
confidence: 99%